Evaluation of project implementation control in pre-construction stage to improve service provider performance in government procurement of goods and services - Siahaan, Apriani; Latief, Yusuf (International research journal of engineering, IT and scientific research, 2025)
This study aims to determine what evaluation activity factors have an impact on the performance of service providers based on Circular Letter No. 18/SE/M/2021 which is carried out on the type of tender/auction with a single-file evaluation method for the kind of procurement of goods/services that uses the lowest price evaluation method of the post-qualification knockout system on projects with a unit price system. This study found that all independent variables, namely arithmetic corrections, conflicts of interest and indications of collusion, administration, qualifications, technical, price and specifications, design and changes, impact the performance of service providers, which are dependent variables. Technical evaluation activities and qualification evaluations have a dominant influence among other variables on the performance of service providers. This research produces modeling and improvements to improve the performance of service providers in the pre-construction stage, which is expected to minimize problems during the project.